RUU KUHAP: Tantangan dan Harmonisasi antara Asas Due Process of Law dan Criminal Justice System di Indonesia - Khairuddin Hasibuan; Budi Sastra Panjaitan; Arifuddin Muda Harahap (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
The renewal of the Criminal Procedure Code (KUHAP) through the Draft Law (RUU) KUHAP opens up space for in-depth philosophical reflection on the relationship between law, justice, and humanity. This article examines the challenges of harmonizing the principle of due process of law, which emphasizes respect for individual rights in every legal process, with the criminal justice system, which is oriented towards efficiency and the purpose of punishment. This harmony is not only a technical and normative matter, but also a matter of shared understanding of what is meant by justice in the context of a more humane and human rights-based criminal justice system. Using a philosophical legal perspective, this article explores the potential for conflict and convergence between the two principles, and seeks common ground within the framework of Pancasila legal values ​​and Islamic law that prioritize humanity, substantive justice, and a balance between individual rights and the public interest. The renewal of the RUU KUHAP, in this context, is not merely a structural change, but a journey towards a legal system that guarantees the depth of justice, which is not only seen from a procedural perspective, but also from the moral and social essence of the law itself.